A Mystical-Political Pledge: The Nexus of the Nazareno Devotion and Politics - Espiritu, Wilson Angelo G (Archīum Ateneo, 2024)
This book explores the potential for the devotional panata (pledge) accorded to the Nazareno of Quiapo, Manila to underscore the inextricable relationship between the mystical and the political dimensions of the Christian faith. Espiritu puts forward a theological model that rejects overemphasis on the panata's mystical quality in favor of a balanced appreciation for its political as well as mystical implications. The central contention is that understanding the panata as "a mystical-political pledge" provides a basis for realizing the political potential of this practice vis-a-vis its mystical character. Should this enriched understanding of the panata reinforce the conscientious political engagement of millions of Nazareno devotees, then this popular devotion would manifest as an effective vehicle for the liberative and transformative grace of Christ in today's Philippine society.